An Effective Phytoconstituent Aconitine: A Realistic Approach for the Treatment of Trigeminal Neuralgia - Dilek Çankal; Esra Küpeli Akkol; Yeliz Kılınç; Mert İlhan; Raffaele Capasso (Mediators of Inflammation)
Trigeminal neuralgia pain remains a challenge to treat. Natural compounds may be promising options for relieving pain. This study was aimed at investigating the effects of aconitine in a rat model of trigeminal neuralgia pain. Infraorbital nerve chronic constriction injury was performed in adult Wistar Albino rats. After the neuropathic pain developed, the rats were assigned to one of the treatment groups: carbamazepine 40 or 80 mg/kg; aconitine 0.25, 0.50, or 0.75 mg/kg; or saline injection (control group). Behavioral testing with von Frey filaments and the rotarod test were carried out before the surgical procedure and on the 24th to 29th postoperative days. Following the completion of tests, ipsilateral and contralateral spinal cords were harvested for Western blot analyses to assess NR-1 protein expression. ANOVA followed by Mann-Whitney U test was performed for the statistical analyses. P values of <0.05 were considered significant. Aconitine significantly reduced mechanical sensitivity in a dose-dependent manner. A significant reduction in motor coordination was noted for the higher doses of aconitine which was similar with the 40 and 80 mg/kg doses of carbamazepine. NR-1 expression was reduced in the ipsilateral spinal cord, whereas no significant difference was noted between the groups in the expression of NR-1 in the contralateral spinal cord. Aconitine had a significant pain relieving effect, which was similar to carbamazepine, in a dose-dependent manner. Aconitine may be an alternative pharmacological agent for the control of trigeminal neuralgia pain.